Chinese Learning Styles Development through Learning by Doing - Yasuttamathada, Nichapha; Nuansri, Adirek (Chophayom Journal, 2021)
The research on the development of Chinese learning model through the process of learning by doing aims to develop Chinese learning model through the process of learning by doing, to study the efficiency of Chinese language skills of learners through learning by doing, and to study the learners’ satisfaction of the learning by doing. The target group used to determine Chinese learning model through learning by doing consisted of 12 instructors and a group of Chinese language experts in higher education level and 75 students who were trained Chinese language from travel retail businesses in the academic year of 2019. Data collected were analyzed by Typological Analysis, Taxonomy Analysis, Statistical Methods and using the dependent sample t-test as statistics. The results revealed that 1) the appropriate form of learning by doing model for creating useful experience and skills in Chinese for students in Chinese language courses should allow all learners to easily learn and understand contents through actual experience whether inside, outside, or from the workplace which will help to build the beneficial skills to work or self-development for students. The integration of Chinese language knowledge with other knowledge could create opportunities for learning with native speakers directly. 2) the student’s achievement after received learning by doing was higher than before receiving learning by doing with statistical significance at the level of .01. 3) all learners were satisfied with learning by doing model at the highest level as overall with the arithmetic means of 4.61. When considered each item, it was found that all items were at the highest level. Keywords: Learning Chinese, learning by doing